PERBANDINGAN ANTARA FILSAFAT EKONOMI ISLAM DAN BARAT - Singgih Muheramtohadi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2018)
Economic philosophy is an undeveloped theme in department of economy. Whereas during the 20th Century there is a clash of two big ideologies that caused by differences in economic philosophy, they are the capitalism and the socialism. These Two big streams often used as comparison object. This Writing, look at the two big streams in a same frame, that is the thought that arise in western worldview which different with Islamic worldview. So it is interesting to study the comparison between philosophy of Islamic economic and western economic through branchs of philosopy, they are ontology, epistemology and axiology.